2021
DOI: 10.1038/s41390-021-01479-6
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric research in the times of COVID-19

Abstract: The COVID-19 pandemic poses many direct and indirect consequences for children’s health and associated research. Direct consequences include participation of children in COVID-19 research trials, pausing other research in children and the potential implications of a global economic downturn on future research funding. Collaborative and networked research together with streamlined research processes and use of remote technology have been central to efforts by clinicians and scientists around the world and have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…14,15 Consequently, dexamethasone use among hospitalized adults with COVID-19 has become routine. 16,17 Although the RECOVERY trial was modified (Version 5) to include children with respiratory COVID-19 infections, 18 few children have been enrolled and no conclusive evidence exists regarding corticosteroid use in this population. In our study, we found no independent association between corticosteroid use and SARS-CoV-2 status among hospitalized children including those admitted to the ICU.…”
Section: Article In Pressmentioning
confidence: 99%
See 2 more Smart Citations
“…14,15 Consequently, dexamethasone use among hospitalized adults with COVID-19 has become routine. 16,17 Although the RECOVERY trial was modified (Version 5) to include children with respiratory COVID-19 infections, 18 few children have been enrolled and no conclusive evidence exists regarding corticosteroid use in this population. In our study, we found no independent association between corticosteroid use and SARS-CoV-2 status among hospitalized children including those admitted to the ICU.…”
Section: Article In Pressmentioning
confidence: 99%
“…27 In January 2021, the situation remained unchanged, with <10% of registered interventional COVID-19 trials including children. 18 The lack of regulatory authorization and high-quality data to guide therapeutic management of children is not a new problem. In the United States, the proportion of medications prescribed to children that are off-label ranges from 62% to 85%.…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…The RECOVERY (Randomised Evaluation of COVID-19 Therapy) trial in the UK involved all age-groups and used innovative methods to ensure rapid recruitment and results with 1000 patients recruited by day 16 of the study. 9 , 10 Van Driest et al discussed techniques to improve engagement with families. Curtailed visiting and outpatient attendance by both parents has been very stressful for parents and impairs practitioner engagement with parents.…”
Section: Children and Familiesmentioning
confidence: 99%
“… 3 5 While federal measures have been proposed to help restore research productivity across all sectors to pre-pandemic levels, there remains limited primary-source data on the impact of the COVID pandemic on pediatric research. 6 – 9 …”
mentioning
confidence: 99%